A comparative evaluation of resin- and varnish-based surface protective agents on glass ionomer cement – a spectrophotometric analysis. Issue 1 (1st January 2020) - Tyagi, Shreya; Thomas, Abi M.; Sinnappah-Kang, Neeta Devi
Abstract: Objectives: To evaluate and compare the effectiveness of resin- and varnish-based surface protective agents on Glass Ionomer Cement (GIC). The different surface protective agents used were: Vaseline ®, GC Fuji VARNISH™ (varnish), G-Coat Plus™ (resin) and EQUIA ® Coat (resin). Method: Thirty-six identical specimens of GIC were made. Six specimens were used in preparation of standard solution and remaining thirty were divided into five groups with six specimens in each group. Each test specimen was coated with one of the surface protecting agent except for the control group. The specimens were immersed separately into 1 ml of 0.05% methylene blue solution for 24 h and then rinsed with deionised water and further immersed into tubes containing 1 ml of 65% nitric acid. Specimens, once completely dissolved in nitric acid solution, were filtered and centrifuged. The supernatant was used to determine the absorbance using a spectrophotometer. The effectiveness of the surface protecting agents for the GIC was recorded in micrograms of dye per specimen, where low values indicate good protection. Result: Tukey HSD test revealed that GC Fuji VARNISH™ (varnish; mean = 21.25 µg/ml), G-Coat Plus™ (resin; mean = 30.39 µg/ml) and EQUIA ® Coat (resin; mean = 9.32 µg/ml) were statistically not significantly different to each other and were effective in protecting the surface of GIC. Significance: The study found that there was a statistically significant difference between control and GC Fuji VARNISH™, G-Coat Plus™ and EQUIA ® Coat. The three agents were found to be equally effective in protecting the surface of GIC.